3‐Dimensional Scanning of Entire Unit Cells in Single Nanoparticles. Issue 5 (28th March 2022) - Heo, Junyoung; Kang, Dohun; Kim, Sungin; Chun, Hoje; Han, Byungchan; Hyo Kim, Byung; Park, Jungwon
Abstract: Properties of nanomaterials such as optical, electrical, and chemical properties are strongly correlated with lattice symmetry, making characterization of lattice symmetry essential. We introduce a symmetry analysis method using 3D atomic coordinates obtained by Brownian one‐particle 3D reconstruction. The method allows direct and quantitative analysis of symmetrical properties and delivers local structural characteristics of individual platinum (Pt) nanoparticles in unit‐cell level. Local structural deformations of the Pt nanoparticles such as lattice distortion and internal symmetry breakage are demonstrated, revealing that the crystal structure of sub‐3 nm Pt nanoparticles generally maintains FCC crystallinity and exhibits localized deviation from their bulk counterpart. Abstract : Characterization of lattice symmetry is important because the symmetry is strongly correlated with physical properties of nanomaterials. We introduce direct and quantitative analysis of lattice symmetry by using 3D atomic coordinates obtained by liquid‐phase TEM. We investigate symmetry of entire unit‐cells composing individual platinum nanoparticles, revealing unique structural characteristics of sub‐3 nm Pt nanoparticles.